Rapid Detection of Toxoplasma gondii Antigen in Experimentally Infected Mice by Dot- ELISA - S Jafar pour Azami; H Keshavarz; M Rezaian; M Mohebali; S Shojaee (Iranian Journal of Parasitology, 2011)
Background: Toxoplasmosis is a worldwide endemic disease. In congenitally infected infants and AIDS patients, toxoplasmosis causes high rates of morbidity and mortality. In these cases antibody detection is difficult; so detection of parasite or its components could be useful tool for early detection and following treatment of the infection.